Effect of Polymer Modified Asphalt With Crumb Rubber on The AC-WC Wear Layer Against Rutting Uses Wheel Tracking Machine (WTM) - Kinanti Wijaya; Sitorus Jeremia; Batubara Hamidun; Sebayang Nono (Journal of Applied Engineering and Technological Science (JAETS), 2026)
Premature rutting remains one of the most critical failure mechanisms in flexible pavements, particularly in tropical regions where high temperatures and increasing axle loads accelerates permanent deformation. Although polymer modified asphalt has been widely investigated to mitigate integration between laboratory rutting performance and statistical prediction models. This study aims to evaluate the effect of crumb rubber (CR) modification on the rutting resistance of Asphalt concrete wearing course (AC-WC) mixtures and to quantify its influence using regression analysis. AC-WC mixtures were prepared with crumb rubber contents of 0%, 5%, 10%, 15% and 20% by weight of asphalt binder, following Indonesian Bina Marga specifications. Rutting performance was assessed using a Wheel Tracking Machine (WTM), while Marshall properties were used to determine optimum asphalt and CR contents. The results indicate that CR contents of 5% and 10% significantly enhance dynamic stability, with the 10% CR mixture exhibiting the highest rutting resistance (1162.7 passes/mm). regression analysis confirms a very strong relationship between CR content and dynamic stability (R2 = 0.979), indicating the dominant role of polymer modification in controlling permanent deformation. These findings demonstrate that crumb rubber improves asphalt elasticity and load distribution under repeated wheel loading the study provides practical implications for sustainable pavement design by promoting waste tire utilization while improving rutting performance in AC-WC layers. The novelty of this research was integrating WTM based rutting evaluation with statistical regression modeling to identify the optimal crumb rubber content for tropical pavement applications.